Crime, corrections, and the COVID-19 Pandemic: responses and adaptations in the U.S. criminal justice system - Pleggenkuhle, Breanne; Schafer, Joseph A. (Perspectives on crime and justice, 2025)
"More than two dozen contributors examine how the social, economic, cultural, legislative, and policy responses to the COVID-19 virus affected crime and justice in the United States"-- Provided by publisher